Analisis Audit Manajemen Pengadaan Barang dan Jasa pada Kasus Bakti Kominfo Berdasarkan Perspektif Kepatuhan Regulasi - Wanda Dea Khairani; Aprita Ravenna Ginting; Cindy Aulia Rusli; Riska Harianingsih; Choms Gary Ganda Tua Sibarani (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study evaluates the management audit of the procurement of goods and services for the 4G Base Transceiver Station (BTS) project managed by BAKTI Kominfo, with a primary focus on compliance with applicable regulations, the effectiveness of internal controls, and deviations at various stages of procurement. A qualitative approach was used, with analysis of documents, official news, and investigative audit findings from BPKP. The results indicate that the project procurement did not comply with Presidential Regulation No. 16 of 2018 and BAKTI Director Regulation No. 7 of 2020, with findings including tender manipulation, weak contract verification, and low levels of transparency. The planning process was also unsupported by adequate feasibility studies, while weak internal oversight exacerbated tender rigging and fund disbursements without proper verification. This study emphasizes the need for improvements in internal oversight, strengthening control mechanisms, and the implementation of e-procurement systems to enhance transparency and accountability in public procurement.